Feasibility, acceptability, and preliminary efficacy of cognitive processing therapy in Japanese patients with posttraumatic stress disorder. Issue 1 (14th December 2022) - Takagishi, Yuriko; Ito, Masaya; Kanie, Ayako; Morita, Nobuaki; Makino, Miyuki; Katayanagi, Akiko; Sato, Tamae; Imamura, Fumi; Nakajima, Satomi; Oe, Yuki; Kashimura, Masami; Kikuchi, Akiko; et al.
Abstract: Cognitive processing therapy (CPT) is one of the most widely tested evidence‐based treatments for posttraumatic stress disorder (PTSD). However, most studies on CPT have been conducted in Western cultural settings. This open‐label, single‐arm trial investigated the feasibility, acceptability, and preliminary efficacy of CPT for treating Japanese patients with PTSD. A total of 25 outpatients underwent 12 CPT sessions. The primary outcome was the assessment of PTSD symptoms using the Clinician‐Administered PTSD Scale for DSM‐IV (CAPS‐IV); secondary outcomes included the assessment of subjective PTSD severity, depressive and anxiety symptoms, trauma‐related cognitions, and subjective quality of life. All outcomes were evaluated at pretreatment (i.e., baseline), posttreatment, and 6‐ and 12‐month follow‐ups. On average, participants attended 13 sessions of CPT ( SD = 1.38), with a completion rate of 96.0%. One serious adverse event (hospitalization) occurred. Significant within‐subjects standardized mean differences in CAPS‐IV scores were found from baseline to treatment completion, g = −2.28, 95% CI [−3.00, −1.56]; 6‐month follow‐up, g = −2.95, 95% CI [−3.79, −2.12]; and 12‐month follow‐up, g = −2.15, 95% CI [−2.89, −1.41]. Moderate‐to‐large effects, g s = −0.77 to −2.45, were found on secondary outcomes. These findings support the feasibility, acceptability, and preliminary efficacy of CPT in a Japanese clinical setting.